Comparative root associated microbial community analysis of Oreocharis mileensis, a resurrection plant species with extremely small populations - Asatulloev, Temur; Yusupov, Ziyoviddin; Cai, Lei; Chen, Qiuping; Gurung, Bishal; Tojibaev, Komiljon Sh.; Sun, Weibang (Frontiers in Microbiology, 2025)
Plants dynamically interact with their microbiomes through phytohormonal signaling and defense responses, shaping microbial diversity and ecosystem function. While resurrection plants host growth-promoting and drought associated microbes, prior studies on different resurrection plants have been limited to localized sampling, potentially underestimating microbial diversity. We analyzed bacterial and fungal communities across five populations of Oreocharis mileensis, a resurrection plant, during hydrated and dehydrated states to examine population-level microbiome differences or affinity, identify microorganisms that may assist during plant desiccation, and assess their conservation across populations. We found that microbial composition was strongly influenced by compartment (bulk soil, rhizosphere, and endosphere) but exhibited only moderate drought-induced changes, suggesting that O. mileensis maintains a stable microbiome under stress. Core phyla (e.g., Proteobacteria, Actinobacteriota, Ascomycota) were conserved across populations, but genus-level core taxa varied relatively between populations, reflecting niche specialization and host genotype. Drought increased bacterial alpha diversity while reducing beta diversity, indicating homogenization driven by stress-tolerant taxa such as Actinobacteriota. Fungal responses differed, with increased beta diversity suggesting drought-enhanced compositional turnover. Key bacterial genera (e.g., Burkholderia-Caballeronia-Paraburkholderia, Bacillus, Rhizobium) dominated hydrated states, while drought enriched Actinobacteria (e.g., Microlunatus, Rubrobacter) and other drought-resistant taxa. Fungal communities shifted from saprotroph-dominated hydrated states to symbiotic taxa (e.g., Paraboeremia, Helotiales) under drought conditions. Functional profiling revealed compartment-specific metabolic specialization, with drought enriching stress-response pathways (e.g., secondary metabolite biosynthesis, signal transduction). These findings demonstrate that O. mileensis microbiomes are structured by compartmental filtering and exhibit drought-driven functional plasticity, with conserved stress-adapted taxa potentially supporting host resilience. Overall, this study expands our understanding of microbiome assembly in resurrection plants and highlights candidate microbes for microbiome engineering to enhance crop stress tolerance.